The Columbia guide to West African literature in English since 1945 - Owomoyela, Oyekan (Columbia guides to literature since 1945., 2008)
"Composed by a premier scholar of African literature, this volume is a comprehensive guide to the literary traditions of Gambia, Sierra Leone, Liberia, Ghana, and Nigeria, five distinct countries bound by their experience with colonialism. Oyekan Owomoyela begins with an overview of the authors, texts, and historical events that have shaped the development of postwar Anglophone literatures in this region, exploring shifts in theme and the role of foreign sponsorship and illuminating recent debates regarding the language, identity, gender, and social commitments of various authors and their works. His introduction concludes with a bibliography of key critical texts.